Modern approaches in sociological theories of religion (Studia Philosophiae Et Juris, 2025)
This article examines contemporary theoretical approaches in the sociology of religion through a comparative analysis of classical and modern sociological paradigms. Drawing on the foundational contributions of Émile Durkheim, Max Weber, and Karl Marx, the study explores how their structural, interpretive, and materialist frameworks have shaped early understandings of religion as a social institution. The article then analyzes key contemporary theories proposed by Jürgen Habermas, José Casanova, Charles Taylor, Colin Campbell, Nancy Ammerman, focusing on concepts such as post-secular society, public religion, moral frameworks, individualization, and lived religion. Methodologically, the study employs a qualitative comparative and interpretive approach, synthesizing classical texts and contemporary theoretical literature. The analysis demonstrates that contemporary sociology of religion moves beyond linear secularization models toward pluralistic, context-sensitive interpretations of religious transformation. Religion is no longer conceptualized merely as a declining institution but as a dynamic cultural, moral, and discursive force actively shaping public life, identity, and social meaning. The findings suggest that modern theoretical approaches enable a more nuanced understanding of religion under conditions of globalization, late modernity, and cultural diversity. The article concludes that contemporary sociology of religion represents a paradigmatic shift toward multidimensional, reflexive, and practice-oriented frameworks, offering significant implications for future empirical research, particularly in post-socialist and non-Western contexts.Шашны социологийн онолын орчин үеийн хандлагуудХураангуй: Энэхүү өгүүлэл нь шашны социологийн орчин үеийн онолын хандлагуудыг сонгодог болон орчин үеийн социологийн парадигмуудын харьцуулсан шинжилгээнд тулгуурлан судалсан болно. Эмиль Дюркгейм, Макс Вебер, Карл Маркс нарын шашныг нийгмийн институц, утга учир, эдийн засаг–нийгмийн харилцаатай холбон тайлбарласан сонгодог онолуудын үзэл санааг үндэс болгон авч, Юрген Хабермас, Хосе Казанова, Чарльз Тэйлор, Колин Кэмпбелл, Нэнси Аммерман нарын орчин үеийн онолчдын постсекуляр нийгэм, олон нийтийн шашин, ёс суртахууны орон зай, хувь хүнчлэл, “амьд шашин” зэрэг үзэл баримтлалуудыг задлан шинжилсэн. Судалгаанд чанарын харьцуулсан, тайлбарлах арга зүйг ашиглаж, сонгодог эх сурвалжууд болон орчин үеийн онолын бүтээлүүдэд суурилсан синтез хийв. Шинжилгээний үр дүнд шашны социологи нь нэг шугаман секулярчлалын загвараас татгалзаж, шашныг институцийн доройтол бус, харин соёл, ёс суртахуун, олон нийтийн харилцаанд идэвхтэй оролцогч динамик хүчин зүйл гэж ойлгох чиг хандлага давамгайлж байгааг харууллаа. Дүгнэж хэлбэл, орчин үеийн онолын хандлагууд нь глобалчлал, орчин үеийн, соёлын олон янз байдлын нөхцөлд шашны өөрчлөлтийг илүү нарийвчлалтай тайлбарлах боломж олгож, постсоциалист болон өрнөд бус нийгмүүдэд чиглэсэн цаашдын эмпирик судалгаанд онолын чухал суурь болж байна.Түлхүүр үгсшашны социологи, секулярчлал, постсекулярчлал, сонгодог онол, орчин үеийн онол, амьд шашин